Methanol extract of Dicranopteris linearis L. leaves impedes acetaminophen-induced liver intoxication partly by enhancing the endogenous antioxidant system - Zainul Amiruddin Zakaria; Farah Hidayah Kamisan; Maizatul Hasyima Omar; Nur Diyana Mahmood; Fezah Othman; Siti Selina Abdul Hamid; Muhammad Nazrul Hakim Abdullah (BMC, 2017)
Abstract Background The present study investigated the potential of methanolic extract of Dicranopteris linearis (MEDL) leaves to attenuate liver intoxication induced by acetaminophen (APAP) in rats. Methods A group of mice (n = 5) treated orally with a single dose (5000 mg/kg) of MEDL was first subjected to the acute toxicity study using the OECD 420 model. In the hepatoprotective study, six groups of rats (n = 6) were used and each received as follows: Group 1 (normal control; pretreated with 10% DMSO (extract's vehicle) followed by treatment with 10% DMSO (hepatotoxin's vehicle) (10% DMSO +10% DMSO)), Group 2 (hepatotoxic control; 10% DMSO +3 g/kg APAP (hepatotoxin)), Group 3 (positive control; 200 mg/kg silymarin +3 g/kg APAP), Group 4 (50 mg/kg MEDL +3 g/kg APAP), Group 5 (250 mg/kg MEDL +3 g/kg APAP) or Group 6 (500 mg/kg MEDL +3 g/kg APAP). The test solutions pre-treatment were made orally once daily for 7 consecutive days, and 1 h after the last test solutions administration (on Day 7th), the rats were treated with vehicle or APAP. Blood were collected from those treated rats for biochemical analyses, which were then euthanized to collect their liver for endogenous antioxidant enzymes determination and histopathological examination. The extract was also subjected to in vitro anti-inflammatory investigation and, HPLC and GCMS analyses. Results Pre-treatment of rats (Group 2) with 10% DMSO failed to attenuate the toxic effect of APAP on the liver as seen under the microscopic examination. This observation was supported by the significant (p < 0.05) increased in the level of serum liver enzymes of alanine transaminase (ALT), aspartate transaminase (AST) and alkaline phosphatase (ALP), and significant (p < 0.05) decreased in the activity of endogenous antioxidant enzymes of catalase (CAT) and superoxide dismutase (SOD) in comparison to Group 1. Pre-treatment with MEDL, at all doses, significantly (p < 0.05) reduced the level of ALT and AST while the levels of CAT and SOD was significantly (p < 0.05) restored to their normal value. Histopathological studies showed remarkable improvement in the liver cells architecture with increase in dose of the extract. MEDL also demonstrated a low to none inhibitory activity against the respective LOX- and NO-mediated inflammatory activity. The HPLC and GCMS analyses of MEDL demonstrated the presence of several non-volatile (such as rutin, gallic acid etc.) and volatile (such as methyl palmitate, shikimic acid etc.) bioactive compounds. Conclusion MEDL exerts hepatoprotective activity against APAP-induced intoxication possibly via its ability to partly activate the endogenous antioxidant system and presence of various volatile and non-volatile bioactive compounds that might act synergistically to enhance the hepatoprotective effect.